PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PANDEMI COVID-19 SEBAGAI VARIABEL MODERASI - Fikri Darmawan (2023)
This research is a quantitative study that aims to determine the effect of capital structure, company growth, and company size on firm value. This study uses non-cyclical industrial companies listed on the Indonesia Stock Exchange for the 2017-2021 period as research samples. The selection of research samples used several criteria, so that only 58 companies could be used as samples of this study. Hypothesis testing was carried out using multiple linear regression analysis with the Stata Program and a significance level of 5%. The results of the test obtained, 1) there is a positive and significant effect of capital structure on firm value, 2) there is no significant effect of company growth on firm value, 3) there is no effect of company size on firm value, 4) the Covid-19 pandemic can moderate the effect capital structure on firm value, 5) the covid-19 pandemic cannot moderate the effect of company growth on firm value, and 6) the covid-19 pandemic can moderate the effect of company size on firm value.